Enhancing Arabic Speaking and Writing Skills through Project-Based Learning: Peningkatan Keterampilan Berbicara dan Menulis Bahasa Arab melalui Pembelajaran Berbasis Proyek - Nila Sari Syafitri; Masturi; Muhammad Hayyis Taqiyuddin; Hisbullah Huda; Moh Al Fayyadh (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2026)
This study aims to examine the effectiveness of Project-Based Learning (PjBL) in enhancing students’ motivation to learn as well as their speaking and writing skills in Arabic. The study employed a quantitative approach with a quasi-experimental design involving 30 participants from Madrasah Aliyah Mambaus Shalihin Gresik, who were divided into experimental and control groups. Data were collected through a learning motivation questionnaire using a Likert scale, as well as through pre- and post-tests to measure speaking and writing skills. The findings indicate that both groups possessed comparable baseline skills. However, following the implementation of the PjBL model, the experimental group demonstrated greater improvement in learning motivation than the control group, with an average score of 82.13%, considered high. Additionally, the experimental group demonstrated superiority in speaking and writing skills, as indicated by final test results and gain scores. Although this model proved effective in creating a dynamic, collaborative, and authentic learning process, there were several challenges in its implementation, including the need for more time, greater teacher attention, and differences in students' participation levels. In practice, these challenges can be addressed by implementing smaller projects, providing clear guidelines, and conducting regular group monitoring, so that teachers at madrasahs can effectively implement PjBL despite limitations in time and supervision. For this reason, the PjBL model is recommended as an innovative approach to improving productive Arabic language skills at madrasahs. Keywords: Learning Motivation, Project-Based Learning, Speaking Skills, Writing Skills